Assessment Of Drought Tolerance in Different Rice Genotypes During Germination and Early Growth Stages by Using Polyethylene Glycol-6000 - Limbu, Anka Kumari; Dhami, Arati; Rawal, Janak Singh; RC, Puspa; Mandal, Ashmita; Awasthi, Renu; Adhikari, Janak (International Journal of Applied Sciences and Biotechnology, 2024)
Rice is a crucial staple food for over half of the global population, particularly in Southeast Asia. However, rice production is increasingly affected by biotic and abiotic stresses, including drought, exacerbated by global climate change. This study explored the effects of negative osmotic pressure induced by polyethylene glycol (PEG-6000) on rice seed germination and growth traits. The experiment was conducted at Gokuleshwor Agriculture and Animal Science College Laboratory, Baitadi, Nepal, using four rice varieties: Black rice, Subha mansuli, Hardinath-4, and Rato basmati. Four osmotic potentials (0, -0.2, -0.4, -0.6 MPa) were applied under controlled conditions. Data on seed germination, root length, shoot length, root-to-shoot ratio, and vigor index were analyzed using two-way ANOVA and LSD tests. Results showed significant differences among rice genotypes and PEG treatments. Rato basmati exhibited the highest germination percentage (78.27%), root length (4.44 cm), shoot length (4.44 cm), and vigor index (718.78), even at -0.6 MPa osmotic potential, indicating superior drought tolerance. Increasing PEG-induced osmotic stress reduced germination and seedling growth across all genotypes. However, Rato basmati’s better performance under -0.6 MPa suggests it as a drought-tolerant genotype, making it a potential candidate for future drought-tolerance breeding programs in rice. Int. J. Appl. Sci. Biotechnol. Vol 12(4): 194-200.